Sorbicillinoid Derivatives From Sponge-Derived Fungus Trichoderma reesei (HN-2016-018) - Rehman, Saif Ur; Yang, Lu-Jia; Zhang, Ya-Hui; Wu, Jing-Shuai; Shi, Ting; Haider, Waqas; Shao, Chang-Lun; Wang, Chang-Yun (Frontiers in Microbiology, 2020)
Six new sorbicillinoids, trichoreeseione A (1) and B (2), trichodermolide B (3), 13-hydroxy-trichodermolide (4), 24-hydroxy-trichodimerol (5), 15-hydroxy-bisvertinol (7), together with three known analogues, trichodimerol (6), 24-hydroxy-bisvertinol (8) and bisvertinol (9), were isolated from the sponge-derived fungus Trichoderma reesei (HN-2016-018). Their structures including absolute configurations were elucidated by analysis of NMR, MS data and calculated ECD spectra. Compounds 1 and 2 with a characteristic naphthalene-trione ring were firstly reported in sorbicillinoid family. Compounds 3 and 4 were two rare sorbicillinoids containing a unique bicycle [3.2.1] lactone skeleton, while 3 with a propan-2-one moiety was also recorded first time in this family. Compound 5 displayed cytotoxic activity against A549, MCF-7 and HCT116 cell lines with the IC50 values of 5.1, 9.5 and 13.7 µM respectively.